21st Century challenges in animal production and food security, additional positive and negative impacts on human health and the environment - Marcelo Ghezzi (Open Journal of Environmental Biology - Peertechz Publications, 2022)
Meat, milk and eggs are nutrient-rich products that could effectively boost nutrient-poor diets, either as part of the normal diet or if access is increased through enrichment with vitamins and minerals, among others. Scientific evidence on the role of livestock products in improving nutrition is limited, especially in low-and middle-income countries, during the first 1,000 days of a child's life. Beyond food production, the livestock sector has additional positive and negative impacts on human health, the environment, societies and economies that must be understood and managed.